2023
DOI: 10.1007/s40801-023-00379-x
|View full text |Cite
|
Sign up to set email alerts
|

Cabozantinib for Advanced Hepatocellular Carcinoma in the Latest Real-World Practice: A Multicenter Retrospective Analysis

Abstract: Background Cabozantinib was found to be effective as a second- or third-line treatment after sorafenib in patients with advanced hepatocellular carcinoma (HCC) in the phase 3 CELESTIAL trial. So far, as immunotherapy has substituted molecular target agents as the primary systemic therapy for advanced HCC, cabozantinib is extensively used in the latest real-world clinical practice in a greatly different position than that shown by the CELESTIAL trial. In the current analysis, we examined the safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…This retrospective analysis suggested that dosing lenvatinib based on body weight in patients with advanced HCC successfully upheld efficacy, with similar rates of treatment-emergent adverse events observed in both body weight groups [121]. There are also data for starting therapy with sorafenib and cabozantinib at a reduced dose, which showed a better side effect profile with preserved anti-tumor activity [122][123][124][125][126][127]. Specifically for hand-foot-syndrome, prophylactic application of emollients containing 10% urea, used two to three times daily, has been demonstrated to decrease the occurrence and postpone the onset of hand-foot syndrome in patients undergoing sorafenib treatment [128].…”
Section: Systemic Treatment Of Hccmentioning
confidence: 90%
“…This retrospective analysis suggested that dosing lenvatinib based on body weight in patients with advanced HCC successfully upheld efficacy, with similar rates of treatment-emergent adverse events observed in both body weight groups [121]. There are also data for starting therapy with sorafenib and cabozantinib at a reduced dose, which showed a better side effect profile with preserved anti-tumor activity [122][123][124][125][126][127]. Specifically for hand-foot-syndrome, prophylactic application of emollients containing 10% urea, used two to three times daily, has been demonstrated to decrease the occurrence and postpone the onset of hand-foot syndrome in patients undergoing sorafenib treatment [128].…”
Section: Systemic Treatment Of Hccmentioning
confidence: 90%
“…Second-line cabozantinib had comparable median OS vs. third- or later-line cabozantinib (8.1 vs. 7.0 months; P = 0.88) [ 79 ]. Third- or earlier-line cabozantinib showed similar median OS (3.2 vs. 4.3 months; P = 0.708) but numerically better PFS compared with fourth- or later-line cabozantinib (9.2 vs. 3.7 months; P = 0.148) [ 80 ].…”
Section: Second-line Therapymentioning
confidence: 99%
“…Third- or earlier-line cabozantinib showed similar median OS (3.2 vs. 4.3 months; P = 0.708) but numerically better PFS compared with fourth- or later-line cabozantinib (9.2 vs. 3.7 months; P = 0.148) [ 80 ].…”
Section: Second-line Therapymentioning
confidence: 99%
See 1 more Smart Citation